Lepidium meyenii Supplemented Diet Modulates Neurobehavioral and Biochemical Parameters in Mice Fed High-Fat High-Sugar Diet - Olofinnade, Anthony T.; Alawode, Abiola; Onaolapo, Adejoke Y.; Onaolapo, Olakunle J. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Metabolic syndrome has been associated with an increased risk of cardiovascular disease, diabetes mellitus, and neurodegenerative disorders. Known side-effects of currently- available drugs necessitate the search for possibly better treatment options. Objective: This study examined the effects of dietary lepidium meyenii (MACA) supplementation on neurobehaviour, metabolic profile, levels of inflammatory markers, and oxidative stress parameters in a mouse model of metabolic syndrome. Methods: Mice were randomly assigned into 8 groups of ten animals each. Groups consist of standard diet (SD) control, high fat/high sugar (HFHS) control and three groups each of lepidium meyenii incorporated into either SD or HFHS diet at 0.1, 0.2 and 0.4%. Mice were fed for seven weeks, and body weight was measured weekly. Open-field behaviors and radial-arm/Y-maze spatial memory were scored at the end of the study. Twenty-four hours after the last behavioral test, fasting blood glucose levels were estimated. Animals were then euthanized, and blood was drawn for estimation of serum lipid profile. Whole brains were excised, weighed and homogenized to estimate the levels of lipid peroxidation, inflammatory markers, antioxidant status, and acetylcholinesterase activity. Results: MACA-supplemented diet was associated with a decrease in body weight gain, an increase in food intake (at lower concentrations), suppression of grooming behavior, and decrease in acetylcholinesterase activity. MACA-supplement also reversed HFHS-induced memory impairment, anxiety, hyperglycaemia, lipid derangement, oxidative stress, and derangement of inflammatory markers. Conclusion: Dietary supplementation with MACA shows beneficial effects in mitigating the effects of metabolic syndrome on the brain in mice.
Keywords: nutraceutical